PARAMOUNT Trial Results - Vinall, Maria (MD Conference Express, 2012)
In about half of all patients with heart failure (HF), the ejection fraction (EF) is normal or nearly normal, despite high morbidity and mortality in these patients. Now, the findings of a Phase 2 trial suggest that a first-in-class angiotensin receptor neprilysin inhibitor, LCZ696, may be beneficial for patients who have HF with preserved EF. This article discusses the Prospective Comparison of ARNI with ARB (angiotensin receptor blocker) on Management of Heart Failure with Preserved Ejection Fraction [PARAMOUNT; NCT00887588] trial.